The macroeconomic stability of United Kingdom after Brexit - Kotliński, Kamil (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: The United Kingdom has been triggered Article 50 of the Lisbon Treaty on 29th March 2017 and formally has been begun Britain’s exit from EU. The Withdrawal Agreement entered into force on 1 February 2020. The very announcement of Brexit aroused many concerns and uncertainty. The Withdrawal has taken place in an orderly manner, the UK and the EU remain in close partnership with new agreements. Such a significant institutional change also may affect economy and indirectly macroeconomic stability. Aim: This research aims to identify and assess the changes in macroeconomic stability in United Kingdom, from the year before the Brexit referendum to the first year outside the EU, i.e. in 2015–2021. Results: The method used in the study is a comparative analysis that employs a macroeconomic stabilization pentagon model (MSP). The macroeconomic stabilization pentagon is based on the GDP growth rate, the unemployment rate, the inflation rate, the budget balance and the current account balance. Time range of research is 2015–2021. The MSP indicators for United Kingdom and EU-27 are compared. In the period 2015–2018, i.e. during the uncertainty as to the results of the Withdrawal Agreement negotiation, the MSP index fluctuates slightly, which we interpret as very small changes in macroeconomic stability. The UK’s macroeconomic stability has fallen dramatically in 2020, the first year out of the EU. It is worth emphasizing that the UK’s macroeconomic stability was lower than EU-27one throughout the period studied.